Differentiable Planning for Optimal Liquidation - Pennacchio, Alan A.; Barros, Leliane N. de; Mauá, Denis D. (Anais do Brazilian Workshop on Artificial Intelligence in Finance (BWAIF), 2022)
Optimal liquidation consists of selling large blocks of single stocks within given time frames optimally with respect to specified risk-sensitive objectives. In this paper, we extend the Almgren-Chriss model for the liquidation process to a more generic and realistic setting and present a differentiable planning algorithm to solve it. We evaluate the performance of the proposed method through experiments, demonstrating the potential of differentiable planning for optimal liquidation in realistic scenarios.